How does multisource feedback influence residency training? A qualitative case study. Issue 6 (16th March 2022) - Hennel, Eva K.; Trachsel, Andrea; Subotic, Ulrike; Lörwald, Andrea C.; Harendza, Sigrid; Huwendiek, Sören
Abstract: Introduction: Multisource feedback (MSF), also called 360‐degree assessment, is one form of assessment used in postgraduate training. However, there is an ongoing discussion on its value, because the factors that influence the impact of MSF and the main impact of MSF are not fully understood. In this study, we investigated both the influencing factors and the impact of MSF on residency training. Methods: We conducted a qualitative case study within the boundaries of the residency training for paediatricians and paediatric surgeons at a University Hospital. We collected data from seven focus group interviews with stakeholders of MSF (residents, raters and supervisors). By performing a reflexive thematic analysis, we extracted the influencing factors and the impact of MSF. Results: We found seven influencing factors: MSF is facilitated by the announcement of a clear goal of MSF, the training of raters on the MSF instrument, a longitudinal approach of observation, timing not too early and not too late during the rotation, narrative comments as part of the ratings, the residents' self‐assessment and a supervisor from the same department. We found three themes on the impact of MSF: MSF supports the professional development of residents, enhances interprofessional teamwork and increases the raters' commitment to the training of residents. Conclusion: This study illuminates the influencing factors and impact of MSF on residency training. We offer novel recommendations on the continuity of observation, the timing during rotations and the role of the supervisor. Moreover, by discussing our results through the lens of identity formation theory, this work advances our conceptual understanding of MSF. We propose identity formation theory as a framework for future research on MSF to leverage the potential of MSF in residency training. Abstract : Hennel et al. use a study of Multisource Feedback to propose identity formation as an important framework for guiding future research in this area.